2017
DOI: 10.1155/2017/9726529
|View full text |Cite
|
Sign up to set email alerts
|

Aeroengine Fault Diagnosis Using Optimized Elman Neural Network

Abstract: A new Elman Neural Network (ENN) optimized by quantum-behaved adaptive particle swarm optimization (QAPSO) is introduced in this paper. According to the root mean square error, QAPSO is used to select the best weights and thresholds of the ENN in training samples. The optimized neural network is applied to aeroengine fault diagnosis and is compared with other optimized ENN, original ENN, BP, and Support Vector Machine (SVM) methods. The results show that the QAPSO-ENN is more accurate and reliable in the aeroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As Figure 3 demonstrated, it encompasses four layers, namely the input layer, the hidden layer, the context links layer, and the output layer [21,22].…”
Section: Theory Behind Elman Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As Figure 3 demonstrated, it encompasses four layers, namely the input layer, the hidden layer, the context links layer, and the output layer [21,22].…”
Section: Theory Behind Elman Neural Networkmentioning
confidence: 99%
“…The ENN model is supposed to have inputs' features { 1 , 2 , … , } , h neurons in the hidden layer { 1 , 2 , … , ℎ } , a context links layer { 1 , 2 , … , } with dimension, and n outputs' signals { 1 , 2 , … , } [19,20,22]. The output signal of the kth context link is defined as:…”
Section: Theory Behind Elman Neural Networkmentioning
confidence: 99%
“…each input layer output is an input to each hidden layer cell. Either the output of the hidden layer is an input to the output layer as well as the input layer, figure (2) shown the Elman Neural Network structure [20]. There are many color systems that can represent the color digital image, and each of these systems have many characteristics that can be used in certain applications, the color system (RGB) is the most color systems used [21][22].…”
Section: Elman Neural Networkmentioning
confidence: 99%
“…18 Pi et al designed a new Elman neural network (ENN) optimized by quantum-behaved adaptive particle swarm optimization (QAPSO) to achieve accurate results in aeroengine fault diagnosis. 19 These studies with classic and typical machine learning methods have demonstrated that the performance of data-based fault diagnosis can be high. However, the widely used feature extraction method may be prone to confusing the fault characteristics due to different fault modes.…”
Section: Introductionmentioning
confidence: 99%